Association of Modified Rankin Scale With Recovery Phenotypes in Patients With Upper Extremity Weakness After Stroke. (3rd May 2022) - Erler, Kimberly S.; Wu, Rui; DiCarlo, Julie A.; Petrilli, Marina F.; Gochyyev, Perman; Hochberg, Leigh R.; Kautz, Steven A.; Schwamm, Lee H.; Cramer, Steven C.; Finklestein, Seth P.; Lin, David J.
Abstract : Background and Objectives: Precise measurement of outcomes is essential for stroke trials and clinical care. Prior research has highlighted conceptual differences between global outcome measures such as the modified Rankin Scale (mRS) and domain-specific measures (e.g., motor, sensory, language or cognitive function). This study related motor phenotypes to the mRS, specifically aiming to determine whether mRS levels distinguish motor impairment and function phenotypes, and to compare mRS outcomes to meaningful changes in impairment and function from acute to subacute recovery after stroke. Methods: Patients with upper extremity weakness after ischemic stroke were assessed with a battery of impairment and functional measures within the first week and at 90 days after stroke. Impairment and functional outcomes were examined in relation to 90-day mRS scores. Clinically meaningful changes in motor impairment, activities of daily living, and mobility were examined in relation to 90-day mRS score. Results: In this cohort of 73 patients with stroke, impairment and functional outcomes were associated with 90-day mRS scores but showed substantial variability within individual mRS levels: within mRS level 2, upper extremity impairment ranged from near hemiplegia (with an upper extremity Fugl-Meyer score 8) to no deficits (upper extremity Fugl-Meyer score 66). Overall, there were few differences in impairment and functional outcomes between adjacent mRS levels. While some outcome measures were significantly different between mRS levels 3 and 4 (Nine-Hole Peg, Leg Motor, gait velocity, Timed Up and Go, NIH Stroke Scale, and Barthel Index), none of the outcome measures differed between mRS levels 1 and 2. Fugl-Meyer and grip strength were not different between any adjacent mRS levels. A substantial number of patients experienced clinically meaningful changes in impairment and function in the first 90 days after stroke but did not achieve good mRS outcome (mRS score ≤ 2). Discussion: The mRS broadly relates to domain-specific outcomes after stroke, confirming its established value in stroke trials, but it does not precisely distinguish differences in impairment and function, nor does it sufficiently capture meaningful clinical changes across impairment, activities of daily living status, and mobility. These findings underscore the potential utility of incorporating detailed phenotypic measures along with the mRS in future stroke trials.